Perancangan furnitur berbasis upcycling waste material batu alam - Gavrila Averina Tirtawijaya; Yusita Kusumarini; Filipus Priyo Suprobo (Institut Seni Indonesia Yogyakarta, 2021)
The use of natural stone in the interior industry is often under-estimated and inefficient. So that unknowingly this causes a lot of waste material from the remaining cutting slabs or stone slabs. Even though if it is reviewed, natural stone waste material has the potential to be recycled into interior products with high aesthetics. In this design the authors collaborate with PT. Gajah Mada Sukses Trinity which is domiciled in Sidoarjo, East Java. This design aims to understand the characteristics of waste material and upcycling techniques that can be applied to highlight its uniqueness. The results of the design in the form of 3 sets of interior product design consisting of coffee tables, side tables, credenza, and console tables, 3 product realization consisting of 2 coffee tables and 1 side table, brands for products & media promotion, and several alternatives compilation of natural stone waste material into mosaic-shaped sheets. This design proves that natural stone waste materials can be reprocessed by upcycling techniques into high-quality interior products.